Perspektif Moral Profesi Guru Milenial: Imperatif Guru-Pelayan - Paulus Tolo (Jurnal Alternatif Wacana Ilmiah Interkultural, 2019)
“Guru” by profession is a leading figure in character building. He is responsible for accompanying his/her students in their search of values. Original meaning of guru is spiritual director who guide ones to reach enlighten and to transfer knowledge. Three major traditions in the East (Hindi, Budhism and Jainism) ascribe guru a high position in religious rites and education. Based on this original meaning of guru, this article tries to adopt it to modern meaning of teacher as a person who provides spiritual and transcendental values to the students. As far as catholic religion teacher concerned, the role of the teacher stemms from his being as a catholic. Being a catholic inspires him to act in accordance to his faith. So, it touches ethics of being and ethics of doing. A catholic religion teacher should regard his profession as a teacher in the service of humanity. One the most difficult problem in the world is the crises of spiritual and transcendetal values. Young milenial students look forward to seeing a teacher who lives these values.